Nonlinear Adaptive Control of Quadrotor - Emran, Bara Jamal (2014)
A Master of Science thesis in Mechatronics Engineering by Bara Jamal Emran entitled, "Nonlinear Adaptive Control of Quadrotor," submitted in February 2014. Thesis advisor is Dr. Aydin Yesildirek. Available are both soft and hard copies of the thesis.